AN ANALYSIS ON THE READING COMPREHENSION ABILITY OF STUDENT SMA NEGERI 5 PONTIANAK - Novisa, Dwi Lusi; Rezeki, Sri Yanti; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is aimed to know how well the reading comprehension ability of the tenth grade students of SMA Negeri 5 Pontianak in Academic Year 2018/2019.The writer used measurement test as techniques to collect the data.The writer classified the result of students? test in order to get the research findings based on the category of the difficulties; main idea, supporting details, vocabulary, and inference and decided the most dominant difficulty faced by the students from each percentage of difficulties.The most dominant problem was made by the students in reading comprehension test was in vocabulary, its percentage with 36%.Where as the other difficulties were supporting details with 28%, reference word with 19% and main idea with 17%. Keywords: Comprehension, Descriptive, Difficulties